Correlation between the chemical order and nature property of Cu-centered Cu-Zr icosahedral clusters. (13th April 2018) - Jiang, Yuan-qi; Peng, Ping
Abstract: Using a first-principles calculation, correlation between the chemical order and nature property of Cu-centered Cu n Zr13- n ( n = 6, 7, 8, 9) icosahedral clusters is investigated. It is found that homogeneous atoms in shell of Cu-Zr icosahedral clusters with low binding energy and high chemical stability prefer to bond each other. In this case, the Cu-Cu interaction is demonstrated to play a key role in the formation of stable Cu-centered Cu-Zr icosahedral clusters. Compared with other metastable Cu-centered Cu-Zr icosahedrons, both of ionic bonding between core and shell Cu atoms and covalent bonding between shell and shell Cu atoms in high stable icosahedrons are strong. An analysis of electronic structures has revealed that this atomic segregation in low energy and high chemical hardness of stable Cu-Zr icosahedral configurations can be attributed to themselves low N ( E F ) at Femi level E F to some extent. A further analysis of Mulliken's population shows these shell Cu atoms are all donees in the formation of Cu-Zr icosahedral cluster, different from the donation of core Cu atoms and shell Zr atoms, and this charge transfer direction does not change with chemical order parameter δ C u Z r and chemical composition of Cu-centered Cu-Zr icosahedral clusters.